Host Modulation Therapy: An Overview - Saurav Panda1, Rinkee Mohanty2, Anurag Satpathy3, Abhaya Chandra Das1, Manoj Kumar1, Rajat Panigrahi (Institute of Medico-legal Publications Pvt Ltd, 2020)
Host modulation therapy involves a wide array of therapeutic strategies directed towards modulation ofhost factors in order to prevent the initiation and progression of periodontal disease. Host modulation is oneof the non-surgical periodontal therapeutic approaches employed nowadays as better compliance is oftenseen among the patients. These strategies are basically aiming at reduction of inflammatory mediators orinhibition of destructive enzymes etc. These approaches are much popular in recent times and employ varioustherapeutics to attain the same. This review enlists the various strategies and approaches in modulating thehost for prevention of periodontal disease.